A Practical Guide to Economic Analysis of Youth Projects - Knowles, James C.; Behrman, Jere R. (World Bank, Washington, DC, 2013)
Investments in youth are particularly important in light of the unprecedented numbers of young people now entering their reproductive and early adult productive years. Of the more than one billion youth aged 15-24, 86 percent live in developing countries. This guide is for those involved in appraising the economic merits of youth projects or projects with an important youth component. It builds on two previous publications in the HNP Discussion Paper series, Assessing the Economic Returns to Investing in Youth in Developing Countries (Knowles and Behrman 2003), and The Economic Returns to Investing in Youth in Developing Countries: A Review of the Literature (Knowles and Behrman 2005). The guide is designed to explain and illustrate basic economic principles relevant to ex ante project appraisal, and their application to the task of making choices related to youth projects. It is also intended to familiarize those who do not specialize in youth projects, with some of the issues particular to youth projects, and to provide some basic understanding of the concepts, relationships and data relevant to undertaking economic analysis of youth projects. The guide comprises seven sections. Following a brief introductory Section 1, Section 2 sketches a framework for economic analysis of youth projects, and the basic economic motives for policies and policy options. Section 3 turns to estimating costs, effectiveness and benefits. Section 4 considers poverty and gender analysis. Section 5 includes seven illustrative case studies covering a variety of youth investments in several different countries. Section 6 presents model terms of reference for the economic analysis of a hypothetical continuing education project in Serbia-Montenegro, corresponding to one of the case studies presented in Section 5. Section 7 provides a list of references.